2014
DOI: 10.1128/jvi.03851-13
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy Enhances Oncolytic Measles Virus Replication by Mitigating DDX58/RIG-I-Like Receptor Signaling

Abstract: The success of future clinical trials with oncolytic viruses depends on the identification and the control of mechanisms that modulate their therapeutic efficacy. In particular, little is known about the role of autophagy in infection by attenuated measles virus of the Edmonston strain (MV-Edm). We investigated the interaction between autophagy, innate immune response, and oncolytic activity of MV-Edm, since the antiviral immune response is a known factor limiting virotherapies. We report that MV-Edm exploits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 43 publications
0
91
0
1
Order By: Relevance
“…Following seasonal influenza A virus infection, receptor interacting protein kinase 2 (RIPK2)-mediated mitophagy reduces immunopathology by negatively regulating activation of NOD-like receptor family pyrin-containing domain protein 3 (NLRP3) signaling and inflammation (Lupfer et al, 2013). We have recently reported that measles virus Edmonston vaccine strain (MV-Edm) infection induces mitophagy in nonsmall cell lung cancer (NSCLC) cells leading to enhanced viral replication (Xia et al, 2014a). While MV-Edm infection induces innate immune responses by means of activation of DDX58/MAVS, it in parallel stimulates SQSTM1-mediated mitophagy to degrade mitochondrion-tethered mitochondrial antiviral signaling protein (MAVS), a key adaptor protein of DDX58/IFIH1 signaling, and thus attenuates antiviral immune responses (Fig.…”
Section: Mitophagy Promotes Viral Replication By Mitigating Antiviralmentioning
confidence: 99%
“…Following seasonal influenza A virus infection, receptor interacting protein kinase 2 (RIPK2)-mediated mitophagy reduces immunopathology by negatively regulating activation of NOD-like receptor family pyrin-containing domain protein 3 (NLRP3) signaling and inflammation (Lupfer et al, 2013). We have recently reported that measles virus Edmonston vaccine strain (MV-Edm) infection induces mitophagy in nonsmall cell lung cancer (NSCLC) cells leading to enhanced viral replication (Xia et al, 2014a). While MV-Edm infection induces innate immune responses by means of activation of DDX58/MAVS, it in parallel stimulates SQSTM1-mediated mitophagy to degrade mitochondrion-tethered mitochondrial antiviral signaling protein (MAVS), a key adaptor protein of DDX58/IFIH1 signaling, and thus attenuates antiviral immune responses (Fig.…”
Section: Mitophagy Promotes Viral Replication By Mitigating Antiviralmentioning
confidence: 99%
“…Some experimental evidences show that autophagy is an essential host defense response to fight infection by destroying infectious pathogens trapped within autophagosomes, and plays an important role in the induction of both innate and adaptive immune response [14, 18, 24-26], whereas some studies show that viruses also subvert autophagy to enhance viral replication and release, such as hepatitis C virus, dengue virus, and measles virus [27-31]. It has been shown recently that NDV strain Beaudette C triggers autophagy both in human U251 glioma cells and in chicken cells leading to enhanced virus replication [32, 33].…”
Section: Introductionmentioning
confidence: 99%
“…AGS7 is caused by gain-of-function variants in IFIH1 , the gene encoding MDA5, which lead to enhanced IFN-β transcription [99]. Autophagy can regulate the activation of mitochondrion-tethered MAVS by mitophagy [100] or other mechanisms [101,102], thus suppressesing type I IFN production. For DNA viruses, cyclic di-nucleotides generated by cyclic GMP–AMP synthase (cGAS) in the presence of dsDNA activate the adaptor protein stimulator of interferon genes (STING) to induce type I IFN expression [97].…”
Section: Autophagy In Other Auids and Differences Between Auids Anmentioning
confidence: 99%